2018
DOI: 10.1186/s41235-018-0114-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving face identification with specialist teams

Abstract: People vary in their ability to identify faces, and this variability is relatively stable across repeated testing. This suggests that recruiting high performers can improve identity verification accuracy in applied settings. Here, we report the first systematic study to evaluate real-world benefits of selecting high performers based on performance in standardized face identification tests. We simulated a recruitment process for a specialist team tasked with detecting fraudulent passport applications. Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 42 publications
4
43
1
Order By: Relevance
“…Although unrelated to our searching task, we considered the relationship between face matching and memory abilities for completeness. Previous research has suggested a moderate to large association between the GFMT and CFMT ( r s = .39—Balsdon, Summersby, Kemp, & White, ; r = .47—Robertson, Jenkins, & Burton, ; r = .45 to .50—McCaffery et al, ). Here, analysing data from our whole sample rather than the unfamiliar judges only (given that no judges were familiar with the models in these two tests), we found a moderate correlation between the two measures of overall percentage correct, r (94) = .34, p < .001.…”
Section: Resultsmentioning
confidence: 94%
“…Although unrelated to our searching task, we considered the relationship between face matching and memory abilities for completeness. Previous research has suggested a moderate to large association between the GFMT and CFMT ( r s = .39—Balsdon, Summersby, Kemp, & White, ; r = .47—Robertson, Jenkins, & Burton, ; r = .45 to .50—McCaffery et al, ). Here, analysing data from our whole sample rather than the unfamiliar judges only (given that no judges were familiar with the models in these two tests), we found a moderate correlation between the two measures of overall percentage correct, r (94) = .34, p < .001.…”
Section: Resultsmentioning
confidence: 94%
“…Thus, it may be that the ability to complete more challenging face recognition tasks reflects properties of the images themselves, rather than different individuals being suited to different tasks. In any case, wider screening of personnel using tasks that directly replicate real‐world needs should be initiated (see Balsdon, Summersby, Kemp, & White, ), and future work might examine the limits of super recognition with regard to image variability.…”
Section: Discussionmentioning
confidence: 99%
“…While the correlation between laboratory‐based and real‐world measures is often difficult to estimate, it is important to quantify where possible. Balsdon, Summersby, Kemp, and White () measured the correlation between the short version of the Cambridge Face Memory Test (CFMT short; 72 items; Duchaine & Nakayama, ), the Glasgow Face Matching Test (GFMT), and a task designed to simulate passport issuance officers’ actual task (i.e., reviewing passport image arrays to decide whether any of the images matched the passport applicant). The CFMT short and the GFMT showed correlations with this real‐world task of r = .41 and r = .46, respectively .…”
Section: Introductionmentioning
confidence: 99%